Analisis Kualitas Sumber Daya Manusia, Upah dan Akses Teknologi Terhadap Tingkat Partisipasi Angkatan Kerja Di Indonesia - Amelia, Febry Wati; Ariusni (Universitas Negeri Padang, 2025)
This study aims to determine how much influence the quality of human resources, wages and access to technology have on the level of labor force participation in Indonesia. This study uses secondary data sourced from the Central Statistics Agency (BPS). With the level of labor force participation as the dependent variable and the independent variables consisting of education, wages, and access to technology and the control variables used are economic growth with a measure of gross regional domestic product. This study uses multiple linear regression methods with panel data in 34 provinces in Indonesia from 2017 to 2023. The model selected in this study is the fixed effect model. The results of the study show that education and gross regional domestic product have a significant positive relationship to the level of labor force participation in Indonesia. The variables wages and access to technology have a positive insignificant relationship to the level of labor force participation in Indonesia.